Enhanced sorbents for the calcium looping cycle and effects of high oxygen concentrations in the calciner - Erans Moreno, Maria (Cranfield University, 2017)
Increasing CO2 emissions from the energy and industrial sectors are a worldwide concern due to the effects that these emissions have on the global climate. Carbon capture and storage has been identified as one of a portfolio of technologies that would mitigate the effects of global warming in the upcoming decades. Calcium looping is a second generation carbon capture technology aimed at reducing the CO2 emissions from the power and industrial sectors. This thesis assesses the improvement of the calcium looping cycle for CO2 capture through enhanced sorbent production and testing at lab-, bench- and pilot-scale, and a new operational mode with high oxygen concentrations in the calciner through experimental campaigns in Cranfield’s 25 kWth pilot unit. Novel biomass-templated sorbents were produced using the pelletisation technique and tested at different conditions in a thermogravimetric analyser (TGA) and a bench-scale plant comprising a bubbling fluidised bed (BFB) reactor. Moreover, the effects of sorbent poisoning by SO2, and the influence of steam were studied in order to explore the effects of real flue gas on this type of material. In addition to the chemical performance, the mechanical strength, i.e. resistance to fragmentation of these materials was tested. In additon, two different kinds of enhanced materials were produced and tested at pilot-scale. Namely, calcium aluminate pellets and HBr-doped limestone were used in experimental campaigns in Cranfield’s 25 kWth pilot plant comprising a CFB carbonator and a BFB calciner. The suitability of these materials for Ca looping was assessed and operation challenges were identified in order to provide a basis for synthetic sorbent testing at a larger scale. Lastly, a new operational mode was tested, which is aimed at reducing the heat provided to the calciner through high oxygen concentration combustion of a hydrocarbon (in this case natural gas) in the calciner. This approach reduces or even eliminates the recirculated CO2 stream in the calciner. In consequence, this results in a lower capital (reduced size of the calciner) and operational cost (less oxygen and less fuel use). Several pilot plant campaigns were performed using limestone as solid sorbent in order to prove this concept, which was successfully verified for concentrations of up to 100% vol oxygen in the inlet to the calciner.
Keywords: Carbon capture; High temperature solid looping; Enhanced CaO-based materials; Pilot plant testing; CO₂ capture performance; Fragmentation